2022
DOI: 10.1186/s12912-022-00904-3
|View full text |Cite
|
Sign up to set email alerts
|

Medication dosage calculation among nursing students: does digital technology make a difference? A literature review

Abstract: Background Patient safety is a major part of nursing care and following patients’ medication orders is considered one of the greatest responsibilities of individual nurses and nursing Failure to make safe drug calculations poses serious risks to patient safety. It is therefore important to strengthen nursing students’ numeracy skills and conceptual abilities during their education. Research suggests that digital technologies play an increasingly important role in promoting nursing students’ kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Mackie and Bruce (45) reported that lessons and online resources designed as an intervention to target mathematical concepts and skills led to improved results and increases in overall pass rates for second-year students for medication dosage calculation tests. Stake-Nilsson et al (41) suggest that digital technologies are increasingly important in promoting nursing students' knowledge and medication dosage calculation skills (36). The results also show that nursing students need more lessons for drug dose calculations that require math skills.…”
Section: Discussionmentioning
confidence: 95%
“…Mackie and Bruce (45) reported that lessons and online resources designed as an intervention to target mathematical concepts and skills led to improved results and increases in overall pass rates for second-year students for medication dosage calculation tests. Stake-Nilsson et al (41) suggest that digital technologies are increasingly important in promoting nursing students' knowledge and medication dosage calculation skills (36). The results also show that nursing students need more lessons for drug dose calculations that require math skills.…”
Section: Discussionmentioning
confidence: 95%
“…Further, there was a significant correlation between BNF and several factors, including the class of antipsychotic, as well as number and type of medications. To this end, several studies have investigated the importance of using TDD calculators for antipsychotic medications( Stake-Nilsson et al, 2022 ). A previous study conclude that calculated dose equivalents based on Defined Daily Doses (DDDs) can be a useful resource for pharmacovigilance studies( Leucht et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…13 The 3 main factors affecting the ability of nurses to correctly calculate medication dosage and identify errors include mathematical abilities, especially the ability to multiply decimal numbers, understand medication formulas, and understand the concept of medication dosage. 14 Both perceptual and computational skills should be considered to improve the method of pharmacological calculations. 15 As a result, having mathematical skills in calculating drug dosage is one of the fundamental principles of safe drug delivery.…”
Section: Methodsmentioning
confidence: 99%